Chronic cavitary pulmonary aspergillosis: Serial clinical and CT findings correlated with antifungal treatment and patient response. Issue 2 (25th October 2022) - Nam, Yoojin; Moon, Seong Mi; Shin, Beomsu; Ko, Nak Gyeong; An, Junho; Wi, Yu Mi; Lee, Kyung Soo
Abstract: Background: Chronic cavitary pulmonary aspergillosis (CCPA) is the most common form of chronic pulmonary aspergillosis. Objective: We hypothesise that by observing serial clinical and CT findings of CCPA patients with antifungal therapy, factors helping predict responses to antifungal therapy could be withdrawn. Methods: A total of 31 patients with CCPA who received antifungal therapy for greater than six months and who had serial CT studies were included. Clinical finding analyses were performed at initial and last follow‐up CT acquisition dates. Clinical characteristics and CT features were compared between clinically improving or stable and deteriorating groups. Results: With antifungal therapy, neutrophil‐to‐lymphocyte ratio (2.66 vs. 5.12, p  = .038) and serum albumin (4.40 vs. 3.85 g/dl, p  = .013) and CRP (1.10 vs. 42.80 mg/L, p  = .007) were different between two groups. With antifungal therapy, meaningful CT change, regardless of clinical response grouping, was decrease in cavity wall thickness (from 13.70 mm to 8.28 mm, p  < .001). But baseline ( p  = .668) and follow‐up ( p  = .278) cavity wall thickness was not different between two groups. In univariate analysis, initial maximum diameter of cavity ( p  = .028; HR [0.983], 95% CI [0.967–0.998]) and concurrent NTM infection ( p  = .030; HR [0.20], 95% CI [0.05–0.86]) were related factors for poor clinical response. Conclusions: With antifungal therapy, cavities demonstrate wall thinning. Of all clinical and radiological findings and their changes, initial large cavity size and concurrent presence of NTM infection are related factors to poor response to antifungal therapy.